Monarchy, the Court, and the Provincial Elite in Early Modern Europe
1 online resource (326 pages)
Keywords: A team of experts view the relationship between rulers and their leading subjects across Europe and further afield. If God-derived authority legitimized a monarch's rule, it did not necessarily prevent opposition to perceived arbitrary government as subjects put forward the counter-concept of consensual rule. The provincial elite might serve the ruler as advisors and officers at court but they also possessed an independent source of power based on their extensive estates. While monarchs wanted to perpetuate a system in which they could watch over members of the regional elite at court and keep them busy, they sought to make use of them as local and provincial administrators, that is, as long as they remained loyal: a fraught balancing act. Contributors include: Hélder Carvalhal, Peter Edwards, Jemma Field, Cailean Gallagher, Pedro José Herades-Ruiz, Graeme S. Millen, Vita MalaÅ¡inskiené, Tibor Monostori, Steve Murdoch, David Potter, Peter S. Roberts, Irene Maria Vicente-Martin, and Matthias Wong.